2017
DOI: 10.1158/1535-7163.mct-16-0728
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance with Epigenetic Alterations Under Long-Term Antiangiogenic Therapy for Hepatocellular Carcinoma

Abstract: Antiangiogenic therapy is initially effective for several solid tumors including hepatocellular carcinoma; however, they finally relapse and progress, resulting in poor prognosis. We here established drug-tolerant subclones of human hepatocellular carcinoma cells by long-term treatment with VEGF receptor (VEGFR) inhibitor and serial transplantation in immunocompromised mice (total 12 months), and then compared them with the parental cells in molecular and biological features. Gene expression profiles elucidate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…We showed that metastatic potentials and gene expression profiles of CSC are regulated by histone modifications for open‐bivalent‐closed chromatin statuses . In our recent studies, sorafenib‐resistant HCC was shown to acquire in vivo CSC features with histone modification . We identified that H3K4me3 and H3K27ac levels were globally elevated in HCC cells surviving under the inhibition of angiogenesis, providing the first evidence that dynamic epigenetic states of CSC could be influenced by modulating the tumor microenvironment in vivo.…”
Section: Cancer Stemness Reprogramming As Therapeutic Resistancementioning
confidence: 86%
“…We showed that metastatic potentials and gene expression profiles of CSC are regulated by histone modifications for open‐bivalent‐closed chromatin statuses . In our recent studies, sorafenib‐resistant HCC was shown to acquire in vivo CSC features with histone modification . We identified that H3K4me3 and H3K27ac levels were globally elevated in HCC cells surviving under the inhibition of angiogenesis, providing the first evidence that dynamic epigenetic states of CSC could be influenced by modulating the tumor microenvironment in vivo.…”
Section: Cancer Stemness Reprogramming As Therapeutic Resistancementioning
confidence: 86%
“…Epigenetic alterations were employed as pivotal mediators of cancer development and drug resistance [25][26][27][28][29]. Histone lysine methylation, maintains by lysine methyltransferases and lysine demethylase, has been involved in both transcriptional repression (H3K9, H3K27 and H4K20) and activation (H3K4, H3K36 and H3K79) [13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic alterations were employed as pivotal mediators of cancer development and drug resistance [25][26][27][28]. Histone lysine methylation, maintains by lysine methyltransferases and lysine demethylase, has been involved in both transcriptional repression (H3K9, H3K27 and H4K20) and activation (H3K4, H3K36 and H3K79) [13,29].…”
Section: Discussionmentioning
confidence: 99%